High facility-level serum potassium variability associated with mortality in hemodialysis patients: results from Chinese Dialysis Outcomes and Practice Patterns Study (DOPPS) - Xinju Zhao; Fan Fan Hou; Xinling Liang; Zhaohui Ni; Xiaonong Chen; Yuqing Chen; Liangying Gan; Li Zuo (Renal Failure)
The role of facility-level serum potassium (sK+) variability (FL-SPV) in dialysis patients has not been extensively studied. This study aimed to evaluate the association between FL-SPV and clinical outcomes in hemodialysis patients using data from the China Dialysis Outcomes and Practice Patterns Study (DOPPS) 5. FL-SPV was defined as the standard deviation (SD) of baseline sK+ of all patients in each dialysis center. The mean and SD values of FL-SPV of all participants were calculated, and patients were divided into the high FL-SPV (>the mean value) and low FL-SPV (≤the mean value) groups. Totally, 1339 patients were included, with a mean FL-SPV of 0.800 mmol/L. Twenty-three centers with 656 patients were in the low FL-SPV group, and 22 centers with 683 patients were in the high FL-SPV group. Multivariate logistic regression analysis showed that liver cirrhosis (OR = 4.682, 95% CI: 1.246–17.593), baseline sK+ (<3.5 vs. 3.5 ≤ sK+ < 5.5 mmol/L, OR = 2.394, 95% CI: 1.095–5.234; ≥5.5 vs. 3.5 ≤ sK+ < 5.5 mmol/L, OR = 1.451, 95% CI: 1.087–1.939), dialysis <3 times/week (OR = 1.472, 95% CI: 1.073–2.020), facility patients’ number (OR = 1.088, 95% CI: 1.058–1.119), serum HCO3– level (OR = 0.952, 95% CI: 0.921–0.984), dialysis vintage (OR = 0.919, 95% CI: 0.888–0.950), other cardiovascular disease (OR = 0.508, 95% CI: 0.369–0.700), and using high-flux dialyzer (OR = 0.425, 95% CI: 0.250–0.724) were independently associated with high FL-SPV (all p < .05). After adjusting potential confounders, high FL-SPV was an independent risk factor for all-cause death (HR = 1.420, 95% CI: 1.044–1.933) and cardiovascular death (HR = 1.827, 95% CI: 1.188–2.810). Enhancing the management of sK+ of hemodialysis patients and reducing FL-SPV may improve patient survival.